Legal Protection of Trade Secrets in Culinary Business Agreements for Micro, Small and Medium Enterprises - M Rizqi Azmi; Dibah, Nabilah Farah; Yuliana Indah Sari (KRTHA BHAYANGKARA, 2025)
All companies have confidential information that is not allowedto be seen by the general public or even known by their employees. In this case, the Indonesian government has enacted laws to protect trade secrets, as local products in Indonesia have high economic value. This article examines the legal protection of trade secrets in culinary business agreementsfor Micro, Small, and Medium Enterprises (MSMEs). And analyzethe challenges faced byMSMEsinthe culinary sectorin implementinglegal protectionoftrade secrets through business agreements. Also, analyzing the implementation of Law No. 30 of 2003 on trade secrets in protecting against violations of trade secrets. The method used in this research is the normativejuridical method by conducting a literature review related to thediscussed issues. The research results show that although the law provides legal protection for trade secrets, in reality, thereare still many information leaks that occur after an employeeleaves the company and joins a competitor. Therefore, it is considered important for business actors to receive legal protection to ensure the implementation of the intellectual property rights system as expected.